2016
DOI: 10.1111/his.13030
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular (blood vessel) histiocytosis with haemophagocytosis

Abstract: This seemingly novel condition is characterized by the presence of histiocytic cells inside blood vessels, where they have not been described previously as an entity. The most reasonable explanation for this process is an origin from the non-classical subset of monocytes that 'patrol' the inner face of blood vessels acting as macrophages. The existence of this entity should be kept in mind to avoid overdiagnosis of malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…10 Our literature review of additional ILH cases after that publication further confirmed the unusual histological finding of multinucleated giant cells in ILH because they were not documented in any subsequent cases. 8,[11][12][13][14][15] Therefore, our case expands the histological spectrum of ILH to include multinucleated giant cells in the intralymphatic histiocytic population. This histological finding is not only of academic interest but may serve as a helpful clue to the nature of the intravascular cellular elements because benign-appearing multinucleated giant cells are not commonly seen in other histological mimickers.…”
Section: Discussionmentioning
confidence: 99%
“…10 Our literature review of additional ILH cases after that publication further confirmed the unusual histological finding of multinucleated giant cells in ILH because they were not documented in any subsequent cases. 8,[11][12][13][14][15] Therefore, our case expands the histological spectrum of ILH to include multinucleated giant cells in the intralymphatic histiocytic population. This histological finding is not only of academic interest but may serve as a helpful clue to the nature of the intravascular cellular elements because benign-appearing multinucleated giant cells are not commonly seen in other histological mimickers.…”
Section: Discussionmentioning
confidence: 99%